Risk Factors Progression Of A Non-Alcoholic Fat Liver Disease And State Of Gut Microflora In Patients With Overbody And Obesity - Daminov Botir Turgunpulatovich, Usmanova Umida Shuhratovna, Alavi Bahromkhon Anishanovich, Sobirova Gozal Naimovna . (International Journal of Advanced Science and Technology, 2020)
Recently, domestic and foreign literature has been actively discussing the growth of non-alcoholic fatty liver disease. In Uzbekistan, the frequency of detection of non-alcoholic fatty liver disease increased from 27.0% in 2007 to 37.1% in 2014 and ranked first among liver diseases.